Analyzing the influence of mobile internet on urban rail transit travel behavior in Chongqing, China: Social informatization as mediating variables - Yuyi Zhu (PLoS ONE, 2025)
The rapid development of mobile internet technology and the widespread adoption of smartphones have significantly influenced people’s daily lives and complicated the mechanisms affecting urban rail transit travel behavior. While existing studies focus predominantly on developed countries, research remains limited in megacities in developing nations experiencing rapid technological growth. Using questionnaire data from urban rail transit travelers in Chongqing, China, this study investigates the intrinsic relationship between mobile internet and residents’ urban rail transit travel behavior, along with its underlying mechanisms. Key findings reveal that: 1) Transportation infrastructure and management informatization directly influence residents’ urban rail transit travel behavior; 2) Transportation services informatization exerts indirect effects; 3) Information literacy and resources mediate the influence of transportation informatization on urban rail transit travel behavior. These findings not only enhance the understanding of how mobile internet is transforming urban rail transit travel behavior but also provide a theoretical foundation for optimizing urban spatial organization in the future.